The deadly don: Vito Genovese mafia boss - DeStefano, Anthony M. (Citadel Press)
Presents the rise and fall of Vito Genovese in this first comprehensive biography of the legendary mafioso--from his childhood in Naples, Italy, and the beginnings of his bullet-ridden criminal career on lower Manhattan's mean streets, through his self-exile in the mid-1930s back to his homeland where he ran a black market operation under the fascist regime of Benito Mussolini, and his return to New York where Genovese made a fortune as the head of an illegal narcotics empire. DeStefano reveals the important and terrifying role Genovese played in the creation of the Mafia, detailing his bloody and ruthless lifetime of crime that would put him behind bars for his last fifteen years--and securing his infamous place in the history of organized crime